To What Extent is Business Responding to Climate Change? Evidence from a Global Wine Producer - Galbreath, Jeremy (2011)
Most studies on climate change response have examined reductions in greenhouse gas (GHG) emissions. Yet these studies do not take into account ecosystem services constraints and biophysical disruptions wrought by climate change that may require broader types of response. By studying a firm in the wine industry and using a research approach not constrained by structured methodologies or biased toward GHG emissions, the findings suggest that both “inside out” and “outside in” actions are taken in response to climate change. While attempts are made by the firm to curtail and reverse climate change through management of carbon emissions, evidence suggests a clear pattern of actions designed to adjust to the adverse consequences of climate change as well. The results both confirm and extend previous findings and suggest that the level and breadth of response to climate change is shaped by situated attention, structural controls, and industry type.
Keywords: Wine; Sustainability; Strategy; Mitigative; Greenhouse gas emissions; Climate Change; Australia; Adaptive